The New Sales Manager : Challenges for the 21st Century. - Vieira, Walter (SAGE India, 2007)
The second edition of The New Sales Manager is an enormously useful. book that provides practical advice and a sound foundation in sales management. to young managers. It is also an interesting, quick revision for senior sales. managers who want to revisit the theory of sales management, in a painless, and. perhaps, entertaining way. Covering the entire range of functions of a sales manager, the book has been. thoroughly revised and includes plenty of illustrations, Real-life anecdotes. and caselets to match the changes in the business environment.